Dance Literacy, Physical Fitness, and Motor Skills Development - Nomer V. Coralde (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study investigated the influence of dance literacy program on the physical fitness and motor skills development of Grade 11 students at Dr. Lorenzo P. Ziga Memorial High School, Pasacao District, Division of Camarines Sur on 2023–2024. Grounded in Motor Learning Theory (2011), the study examined how dance literacy can enhance students’ physical, social, and emotional development. The study also determined students’ levels of physical fitness and motor skills development within gross and fine motor domains. The study also analyzed the relationships between dance literacy and physical fitness and between dance literacy and motor skills development. It employed descriptive-correlational research design with 53 Grade 11 students who were selected through total enumeration. The data utilized survey questionnaires and semi-structured interviews and were treated through mean, Pearson correlation and coefficient of determination. The findings showed that the students reached excellent levels of physical fitness in cardiovascular and muscular endurance while muscular strength was rated only at a good level since there was limited resistance trainings. In general, the students exhibited excellent level of gross motor skills but their fine motor skills remained at a good level. The results also revealed that there is no significant relationship between dance literacy and physical fitness and between dance literacy and motor skills development. The study suggests to integrate resistance trainings to strengthen the abdominal and back muscles and model the technicalities of intricate movements of hands and fingers like creating small cursive or zigzag strokes.